The status of intensive care medicine research and a future agenda for very old patients in the ICU - Flaatten, H.; de Lange, D. W.; Artigas, A.; Bin, D.; Moreno, R.; Christensen, S.; Joynt, G. M.; Bagshaw, Sean M.; Sprung, C. L.; Benoit, D.; Soares, M.; Guidet, B. (Intensive care medicine, 2017)
The “very old intensive care patients” (abbreviated to VOPs; greater than 80 years old) are probably the fastest expanding subgroup of all intensive care unit (ICU) patients. Up until recently most ICU physicians have been reluctant to admit these VOPs. The general consensus was that there was little survival to gain and the incremental life expectancy of ICU admission was considered too small. Several publications have questioned this belief, but others have confirmed the poor long-term mortality rates in VOPs. More appropriate triage (resource limitation enforced decisions), admission decisions based on shared decision-making and improved prediction models are also needed for this particular patient group. Here, an expert panel proposes a research agenda for VOPs for the coming years.